Segmental quantification of hepatic lipid content based on volumetric MRI data in patients with suspected iron overload - Wunderlich, Arthur P.; Cario, Holger; Kannengießer, Stephan; Grunau, Veronika; Götz, Michael; Hüttner, Felix; Backhus, Johanna; Beer, Meinrad; Schmidt, Stefan Andreas (RöFo - Fortschritte auf dem Gebiet der Röntgenstrahlen und der bildgebenden Verfahren, 2023)
Purpose To investigate the segmental distribution of hepatic fat fraction, determined with MRI (MR proton density fat fraction, short MR-PDFF) in patients suspected of having liver iron overload.Methods The liver of 44 patients examined with MRI using a 3D multi-echo gradient-echo sequence was segmented semiautomatically and subdivided into nine segments (segment 4 divided in 4a and 4b). Segmental fat content was determined on MR-PDFF maps. Whole-liver steatosis grades were compared to those found in individual segments. Segmental MR-PDFF differences were tested for statistical significance.Results The most common diseases were thalassemia, various forms of anemia, and hereditary hemochromatosis. No patients suffered from fat metabolism disease. Iron overload was present in 37/44 (84 %) patients. For the whole liver, 22 patients showed a steatosis grade of 0, 21 patients were graded S1, and one patient had a steatosis grade of 2. The grade of steatosis was underestimated in 5 of 21 patients (24 %) in segment 8 and in 8 of 21 patients (38 %) in segment 7. Highly significant segmental MR-PDFF differences were detected with p < 0.00 001, e. g., comparing segment 2 to 5. Segments 1 to 3 had the highest fat content, segments 7 and 8 had the lowest.Conclusion Our results suggest that the storage of fat in the liver is inhomogeneous, so that segment-wise differing fat concentrations were found. Fat distribution in patients with suspected hepatic iron overload was similar to living liver donors. However, it showed significant differences compared with the values published for NAFLD patients, which were less pronounced in the group with high average hepatic MR-PDFF values than in the group with normal lipid content. In patients suspected of having iron overload, segment 8, which is mainly targeted for biopsy, and segment 7 may underestimate steatosis grade.Key Points:
Keywords: MR-imaging; hepatic MR-PDFF; NAFLD; liver iron overload; thalassemia